SOFTWARE-TOOL PLATFORM OF DIDACTIC DESIGN OF INFORMATION LEARNING ENVIRONMENT IN SECONDARY EDUCATION - Shevchenko, V.L.; Vasilchenko, L.V.; Gavrish, D.V.; Vetchynkin, O.S. (Journal of Information Technologies in Education (ITE), 2010)
In the article considered problems of theoretical meaning in the context of terminology that used in distance education, practical aspects of designing methods of didactic implementation and practical solutions as for to organization of information education environment and personal-oriented implementation of its educational process in secondary general education school.